Pengembangan Media Pembelajaran Pendidikan Agama Islam Berbasis Website di SMPIT Al-Husnah Lebong - Meiyanda, Rana; Mahardika, Mutiara; Asbabul Jannah, Wahyu; Gunawan, Guntur; Kusen (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study aims to develop a web-based Islamic Education learning media using the Research and Development (R&D) approach with the ADDIE model up to the implementation stage. The need analysis indicates several persistent issues in Islamic Education classrooms, including teacher-centered instructional methods, limited instructional hours, restricted access to textbooks, and varied student learning abilities. These issues highlight the urgency of developing flexible, multimodal, and interactive digital learning resources. The product was developed through structured stages, including content formulation, interface design, WordPress installation, Tutor LMS configuration, and multimedia integration. Expert validation resulted in excellent scores: 90% from the material expert, 92.5% from the IT expert, and 95% from the teaching practitioner. The feasibility test involving 35 students also showed highly positive results, with 83.57% for operational ease, 89.29% for visual and content presentation, and 89.46% for learning effects. n terms of state of the art, this study contributes to the growing body of digital Islamic Education research that increasingly emphasizes interactive web-based platforms, moving beyond traditional printed modules, Android-based apps, or video-centered media commonly found in previous studies. By integrating WordPress and Tutor LMS, this research demonstrates the potential of open-source LMS ecosystems to provide scalable, accessible, and pedagogically rich learning environments suitable for Islamic Education contexts. The findings confirm that the developed media is feasible, user-friendly, and capable of fostering motivation, independent learning, and meaningful engagement. Future research should investigate the media’s effectiveness on learning outcomes, explore gamification-based interaction, and integrate advanced learning analytics to enhance personalized Islamic Education learning pathways.